2018
DOI: 10.3389/fmicb.2018.02385
|View full text |Cite
|
Sign up to set email alerts
|

Thioredoxin Profiling of Multiple Thioredoxin-Like Proteins in Staphylococcus aureus

Abstract: Hydrogen sulfide (H2S) is thought to signal through protein S-sulfuration (persulfidation; S-sulfhydration) in both mammalian systems and bacteria. We previously profiled proteome S-sulfuration in Staphylococcus aureus (S. aureus) and identified two thioredoxin-like proteins, designated TrxP and TrxQ, that were capable of reducing protein persulfides as a potential regulatory mechanism. In this study, we further characterize TrxP, TrxQ and the canonical thioredoxin, TrxA, by identifying candidate protein subst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 40 publications
(90 reference statements)
0
17
0
Order By: Relevance
“…Peng et al studied the reactivity of TrxA, TrxP, and TrxQ from Staphylococcus aureus with persulphidated pyruvate kinase as a model substrate. The three redoxins displayed small differences in substrate specificity that were also discussed to be the result of electrostatic differences in the area surrounding the N-terminal active site thiol [79]. We have previously proposed and provided evidence that the binding of Trx family proteins to their interaction partners and likely all protein-protein interactions in aqueous solution require geometrically compatible surfaces and, that given, are controlled by complementary electrostatic surfaces [14,39,80].…”
Section: Discussionmentioning
confidence: 98%
“…Peng et al studied the reactivity of TrxA, TrxP, and TrxQ from Staphylococcus aureus with persulphidated pyruvate kinase as a model substrate. The three redoxins displayed small differences in substrate specificity that were also discussed to be the result of electrostatic differences in the area surrounding the N-terminal active site thiol [79]. We have previously proposed and provided evidence that the binding of Trx family proteins to their interaction partners and likely all protein-protein interactions in aqueous solution require geometrically compatible surfaces and, that given, are controlled by complementary electrostatic surfaces [14,39,80].…”
Section: Discussionmentioning
confidence: 98%
“…In this study, B. cereus showed much higher disulfide reducibility among E. coli , P. aeruginosa and B. subtilis . Besides, a previous study identified two thioredoxin-like proteins TrxP and TrxQ, which could reduce protein disulfide as a potential regulatory mechanism [ 47 ]. This may account for the highest disulfide reducibility of S. aureus among other strains.…”
Section: Discussionmentioning
confidence: 99%
“…The characterization of two thioredoxins in S. aureus that have significant activities on protein persulfides relative to disulfides versus the canonical TrxA certainly suggests a role for Trx in this process, as well as the possibility that bacteria encode specific thioredoxin-like proteins for this purpose (96). Furthermore, a thioredoxin-based proteomic profiling strategy was used to identify potential cellular targets for these persulfide-reducing thioredoxins in S. aureus (193). Analogous strategies might be applied to STRs in an effort to identify protein targets that could function as donors or acceptors in transsulfuration reactions.…”
Section: H 2 S Signaling Via Protein S-sulfurationmentioning
confidence: 99%